Grand investment of tourism sector effort to make many villas and hotels for expanding work opportunities on budgeting - Sunariani, Ni Nyoman; Maheswari, A. A. Istri A.; Pemayun, A. A. Gde Putra (International research journal of management, IT and social sciences, 2019)
This research discussed grand investment tourism sector efforts to increase the number of villas and hotels to expand employment opportunities in the Sub-district of Ubud Bali." affect the economic growth of a region. The main problem is how is the tourism sector’s grand investment effort to increase the number of villas and hotels to expand employment opportunities in the Sub-district of Ubud Bali? High levels of unemployment can increase the amount of crime and increase social unrest. If examined further, from an economic standpoint, if many foreign and local investments are realized then job opportunities are wide open for the people in the area and other regions so that people’s income rises by itself. The government is trying to create vocational education that aims to produce a quality and superior workforce in all sectors. Investment activities are the use of a sum of money in the hope of obtaining benefits and can plan their financing and implementation as a unit of activity within a certain period of time. Expenditure on investment costs is done once and only produces benefits a few years later.